Analisis Penyebab Perceraian di Bangkalan - Ayu Lintang Priyan Andari; Nur Aini Risqi Yolandari; Almira Kadiva Khanza Rana; Uswatun Hasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy family, sakinah mawaddah warahmai. However, it is possible that there will be disharmony with the purpose of marriage, namely disputes in the household. Continuous disputes can result in divorce where this divorce is not in accordance with the principle of monogamy. This study uses a normative method with a technique of collecting materials in the form of literature and interviews with receptionists at the Religious Court and Advocates. The legal consequences of divorce for children who are victims of divorce so they must be maintained both materially and non-materially until they are adults (mummayiz). The legal consequences for ex-wives are alimony in the form of iddah and mut'ah if requested to the Court and granted. There is a division of joint property during marriage.